Kenya's Climate Smart Governance Dashboard: training manual - Alahacoon, Niranga; Amarnath, Giriraj (International Water Management Institute (IWMI), 2024)
Kenya’s unique geographical location and diverse ecosystems make it highly vulnerable to various climate hazards, including floods, droughts, landslides, and cyclones. These hazards significantly impact the country's economy, livelihoods, and natural resources, emphasizing the need for robust adaptation measures, early warning systems, and sustainable climate-smart policies to ensure resilience and sustainable development.